Development of forced degradation and stability indicating studies of drugsâA review - M Blessy; Ruchi D. Patel; Prajesh N. Prajapati; Y.K. Agrawal (Elsevier, 2014)
Forced degradation is a degradation of new drug substance and drug product at conditions more severe than accelerated conditions. It is required to demonstrate specificity of stability indicating methods and also provides an insight into degradation pathways and degradation products of the drug substance and helps in elucidation of the structure of the degradation products. Forced degradation studies show the chemical behavior of the molecule which in turn helps in the development of formulation and package. In addition, the regulatory guidance is very general and does not explain about the performance of forced degradation studies. Thus, this review discusses the current trends in performance of forced degradation studies by providing a strategy for conducting studies on degradation mechanisms and also describes the analytical methods helpful for development of stability indicating method. Keywords: Degradation conditions, Degradation product, Forced degradation, Stability indicating method, Stress testing